2004
DOI: 10.1007/s11748-004-0118-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct cannulation of the common carotid artery during the ascending aortic or aortic arch replacement

Abstract: Direct cannulation of the common carotid artery is a simple, safe, and acceptable cerebral protection for patients undergoing aortic or aortic arch replacement procedures in the patients with these specific conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…The combined approach seemed to be too invasive for respiratory function. On the other hand, Ohata et al [2] found no significant differences in respiratory function or in the inflammatory response between patients who underwent total arch replacement through a median sternotomy and those who also had a left anterolateral thoracotomy. Especially in the distal reoperative situation for dissecting type A, the retrosternal space can be easily excised from a left thoracotomy, although adhesion due to previous surgeries can be moderate or severe.…”
Section: Discussionmentioning
confidence: 96%
“…The combined approach seemed to be too invasive for respiratory function. On the other hand, Ohata et al [2] found no significant differences in respiratory function or in the inflammatory response between patients who underwent total arch replacement through a median sternotomy and those who also had a left anterolateral thoracotomy. Especially in the distal reoperative situation for dissecting type A, the retrosternal space can be easily excised from a left thoracotomy, although adhesion due to previous surgeries can be moderate or severe.…”
Section: Discussionmentioning
confidence: 96%
“…39 Rylski and colleagues 43 very comprehensively outlined the different cerebral protection strategies in ATAAD surgery complicated by cerebral malperfusion. According to them, carotid artery cannulation, although relatively limited in clinical experience, 45,46 can potentially provide several benefits: easy surgical access; wider and stronger arterial walls compared to the AxA, which makes its cannulation feasible in obese patients requiring high CPB flow; and unlike the axillary and innominate arteries that are only limited to the right side, both the right and left carotid arteries can be cannulated for cerebral perfusion. In the case of carotid dissection, they also emphasized the effectiveness and ease of combining carotid cannulation with a 2nd or 3rd arterial line to ensure both cerebral and systemic perfusion.…”
Section: Cerebral Protection Strategies and Monitoringmentioning
confidence: 99%
“…Despite advances in surgical techniques, including anesthesia and cardiopulmonary bypass (CPB), brain injury after aortic arch surgery remains an important source of morbidity and mortality because of the advanced age of the patients and the presence of serious comorbidities. [1][2][3][4][5][6] Extended thoracic aortic aneurysms involving the ascending aorta, arch, and descending aorta are often repaired in staged operations. 7 However, single-stage replacement of the aortic arch and descending aorta might be a preferable surgical option for specific types of atherosclerotic aneurysm such as chronic type A or B dissection.…”
Section: Introductionmentioning
confidence: 99%